Africa - are small- and medium-sized enterprises wasting chances?. (2016) - Stuetzel, Moritz; Neubert, Michael
This multiple case study looks at promising forms of market entry by German-speaking SMEs in the engineering industry in Africa. Kenya was selected as an example for this study. In an empirical study, which is built on the issue was investigated using qualitative in-depth interviews with subject matter experts. In addition to this, the market attractiveness of Kenya and examples of successful market entry were analysed. The results of the multiple case studies were clustered and evaluated using triangulation. The research results confirm that the selection of the market entry form depends greatly on the market attractiveness. In the first phase of market entry, direct export in collaboration with local distributors who help to bridge differences in the market and with obtaining initial customers dominates. Sustainable market success only develops, however, if SMEs are willing to engage with the market and adjust what they offer to the local requirements.